The Application of the Discovery Learning Model in Improving Religious Understanding of Students in the Lessons of the Book of Sulam Al-Taufīq - Abdul Mun’im Amaly; Supiana Supiana; Tedi Priatna; Karman Karman (Jurnal sosial dan sains, 2024)
Background: Understanding of the material of the book is difficult, it is not surprising to question whether the understanding of the material has become neglected. Therefore, the religious understanding of students must be developed by the ustāẓ in the Islamic boarding school through the learning process. This can be done using the formulation of the discovery learning model which contains a comprehensive learning procedure design. Purpose:. This study aims to determine the application of the discovery learning model, and the religious understanding of students using discovery learning and non-discovery learning models, as well as increasing the religious understanding of students after using discovery learning and non-discovery learning models in Class 1 Aliyah Darul Falah Islamic Boarding School and Al-Mukhtariyah Islamic Boarding School West Bandung Method:. The research approach used is an experimental study with a quasi-experimental type in the form of a nonequivalent pre-test and post-test control group design. The research population was students of Class 1 Aliyah Darul Falah Islamic Boarding School and Al-Mukhtariyah Islamic Boarding School, West Bandung with a sample of 106 students consisting of experimental and control classes. The research instrument used was a 38-item questionnaire, providing 20 multiple-choice questions and 5 description questions. Data were analyzed using statistical tests Results: The results of the research show that the discovery learning model is very suitable to be applied to the Al-Taufīq Sulam Book lesson, at the Darul Falah Islamic boarding school it got an average score of 93.65% which shows a very good interpretation value, and at the Al-Mukhtariyah Islamic boarding school, it got an average score of 93.65%. an average of 90.42% which shows a very good interpretation value. The religious understanding of students using the discovery learning model at the Darul Falah Islamic boarding school is at high criteria with an average pretest score of 52.39 and posttest 82.85 which has increased by 30.46%, at Al-Mukhtariyah Islamic boarding school it is at sufficient criteria. The average pretest score was 43.57 and posttest 75.87, which was an increase of 32.3%. Conclusion: Meanwhile, non-discovery learning at the Darul Falah Islamic boarding school is at sufficient criteria with an average pretest score of 58.44 and posttest of 70.22, an increase of 11.78%, at the Al-Mukhtariyah Islamic boarding school it is at sufficient criteria with an average score -average pretest 51.22 and posttest 60.65, an increase of 9.43%